Drought stress induced modification on growth and Pigments composition in different genotypes of Helianthus annuus L. - Rabert, Mahalingam Rajasekar, R. Somasundaram, Paramasivam Manivannan, Gabriel Amalan (Current Botany, 2015)
In this investigation, a pot culture experiment was conducted to estimate the ameliorating effect of drought stress Induced modification on various growth and Pigments composition in different genotypes of Helianthus annuus L. (Sunflower). Economically important oil seed crop sunflower five cultivars viz., Asgrow SH 3322 (A-SH 3322), Agsun 110 (A-110), Kaveri 618 (K-618), SH 416, and Sunbred 275 (S-275) were selected for drought analysis. Plant growth and productivity is adversely affected by natureâ€™s wrath in the form of various biotic and abiotic stress factors. Water deficit is one of the major abiotic stresses, whichÂ Â adversely affects crop growth and yield. 3, 4 and 5 DID was selected for the drought stress treatments. Drought stress causes considerable decreases in growth and pigments content of sunflower. Among the cultivar K-618 was less affected by the drought and to it had increased root length and near normal vegetative and shoot growth during stress and at stress recovery. The growth parameters and pigment total chlorophyll and carotenoid content decreased under drought stress in all the sunflower cultivars. Among the cultivars the S-275 cultivar was severely affected when compared to other cultivars.